Assessment of Oxidative Stress and Inflammatory Cytokines and renal functions markers in Patients with Oral Squamous Cell Carcinoma Before and After Surgical Resection - Ali Saqlain Haider, Muhammad Zahid Ishaq, Muhammad Hamza Hashim, Saiha Muneer, Anam Asif, Nadeem Abbas (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Oral squamous cell carcinoma (OSCC) is characterized by local malignancy and systemicperturbations including oxidative stress, inflammation, and potential impact on renal function. Thisexperimental longitudinal study aimed to evaluate changes in oxidative stress markers (malondialdehyde